PERAN FATWA MAJELIS ULAMA INDONESIA (MUI) DALAM PEMBANGUNAN HUKUM DI INDONESIA: Yuli Darti - admin, admin (Reformasi Hukum, 2017)
For the sake of the creation of good legal development needs the cooperation between government and social institutions. One of the social institutions that have an important role in development is the Indonesian Council of Ulama (MUI), among the MUI's task is to give a fatwa. The birth of the MUI fatwa became very important as an expression of the legal needs of society (Muslims) as well as in response to the growing problems, which derive from Islamic law as living law. The metdology used is an normative juridical research. This research concludes that MUI fatwa is very important in the development of law in Indonesia, including: (1) As reference or references in the formulation of legislation; (2) As the legal opinion and advocate base used in the judicial process, as well as evidence in court or in other words MUI fatwa used as referral of investigator in conducting investigation. And the determination of a fatwa, MUI must go through the procedures in the provisions that have been formulated. One of the roles of MUI fatwa whose influence is felt is very important in the development of law in Indonesia is the birth of Law No. 21 of 2008 on Sharia Banking, whose basic content is based on MUI fatwa. With the birth of Law No. 21 of 2008 on Sharia Banking as evidence that in its development, MUI Fatwa can be the answer or solution of problems that arise in a developing society. Whether it is the economic, social, cultural, and spiritual problems of society, it is also a proof that the MUI fatwa can be binding as long as it is absorbed into legislation.